PERANCANGAN VISUAL IDENTITY UDA CAFE TALU PASAMAN BARAT - ADRIA APRIL ZONNIKA, Dini Faisal, S.Ds., M.Ds., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
UDA cafe was founded by Riskyrana Lukman in 2016, having his address at 11 Wirataman Street, Kenagarian Talu, West Pasaman Regency. The absence of visual identity that still greatly influences the existence and image of its business, so it requires the design of a visual identity in the form of a logo with color and typography that represents the concept of the UDA cafe. The design goal is a manifestation of the writer's desire to build a new identity and positive image, and get a good positioning in the minds of consumers, which aims to gain brand awareness and brand loyalty towards the UDA cafe.The analytical method used in designing visual identity of the UDA cafe uses the SWOT analysis method (Strangh, Weakness, Opportunity, Threat) The orientation of developing visual identity design ideas includes the main media in the form of neon boxes and supporting media in the form of manual books, chainfag, x-banner , T-shirts, aprons, hats, menu lists, key chains, mugs, business cards, stickers. It is expected that with this visual identity design can help create positioning and get brand awareness so that the design results are targeted, effective and communicative so that they can be known by the wider community.Keywords : Visual Identity, Design, UDA cafe, Image